1999
DOI: 10.1034/j.1399-0039.1999.540307.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA and tumour necrosis factor (TNF) polymorphisms in ocular Behçet’s disease

Abstract: The role of HLA-B*51 and other major histocompatibility complex (MHC) genes in Behçet's disease (BD) remains unknown. We have performed HLA and tumour necrosis factor (TNF) polymorphism analysis in BD and evaluated their contribution to ocular disease. In this study, 102 patients and 115 controls of Middle Eastern descent were investigated by HLA and B*51 subtyping using novel primers, and by LT alpha NCo 1 and TNF 308 promoter polymorphism analysis. The frequency of the HLA-B*51 family of alleles was raised i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
2
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(64 citation statements)
references
References 20 publications
3
57
2
2
Order By: Relevance
“…The TNF promoter allele TNF-1031C has been recently reported to be associated with BD susceptibility in Caucasoid patients, 110 and the co-expression of the TNF-β*2 allele with HLA-B*51 has also been found to contribute to the severity of ocular disease. 111 More recently, it has been shown that susceptibility to BD has also been documented to be significantly increased in patients carrying the IL-1β +3953T allele and TT genotype, which correlate with increased IL-1β secretion in vitro. 112 IL-1β levels appear to be not significantly different from controls in the aqueous humor of BD-associated uveitis in a recent study of five samples, but it is not clear whether these patients were on treatment at the time of sampling.…”
Section: Behçet's Diseasementioning
confidence: 99%
“…The TNF promoter allele TNF-1031C has been recently reported to be associated with BD susceptibility in Caucasoid patients, 110 and the co-expression of the TNF-β*2 allele with HLA-B*51 has also been found to contribute to the severity of ocular disease. 111 More recently, it has been shown that susceptibility to BD has also been documented to be significantly increased in patients carrying the IL-1β +3953T allele and TT genotype, which correlate with increased IL-1β secretion in vitro. 112 IL-1β levels appear to be not significantly different from controls in the aqueous humor of BD-associated uveitis in a recent study of five samples, but it is not clear whether these patients were on treatment at the time of sampling.…”
Section: Behçet's Diseasementioning
confidence: 99%
“…Dieser Genotyp liegt bei ca. 40-80% der MB-Patienten vor, während dies in einer gesunden Vergleichspopulation bei nur 8% (Europa) und 24% (Türkei) der Fall ist [28]. Je nach geografischer Verteilung erhöht sich das relative Risiko, einen MB zu entwickeln, bei HLA-B51 + -Individuen auf 1,4 in Portugal, in Deutschland auf ca.…”
Section: Genetikunclassified
“…Genetische Untersuchungen konnten eine Assoziation dieser seltenen Erkrankung mit dem HLA B51-Allel zeigen (20). Andere Arbeitsgruppen betonen die pathogenetische Bedeutung von erhöhten c d-T-Zellzahlen im peripheren Blut sowie die Wirkung der sekretierten Immunmediatoren TNF-a, Inteferon-c, der autoreaktiven Th1-Zytokine und Interleukin-12 (7).…”
Section: Diskussionunclassified